CHARACTERIZATION OF MESENCHYMAL STEM CELLS FROM WHITE ADIPOSE TISSUE OF Macaca fascicularis - Harrold Halilintar MR Subu Taopan; Fitriya Nur Annisa Dewi; Silmi Mariya; Huda Darusman; Permanawati Permanawati; Dondin Sajuthi; Irma Herawati Suparto (Jurnal Kedokteran Hewan, 2021)
Mesenchymal stem cells (MSC) derived from white adipose tissue are considered to be an appropriate therapeutic candidate for various human diseases due to their natural ability to maintain homeostasis. They have also been considered for use as a therapeutic alternative due to their sufficient availability and ease of harvesting. MSC play an important role in the process of adipogenesis and energy metabolism that is directly related to the pathogenesis of various degenerative diseases and metabolic syndromes. The purpose of this study was to obtain MSC cultures from white adipose tissue biopsied from three adult males Macaca fascicularis and to evaluate these cultures qualitatively and quantitatively regarding their characteristics and ability to differentiate. Polymerase chain reaction (PCR) was used to confirm the expression of mesenchymal stem cell-specific gene markers, and a specific growth medium was used to differentiate these cells into adipocytes, chondrocytes, and osteocytes. The results obtained showed that the MSC culture from M. fascicularis WAT had a fibroblast-like morphology with a spindle shape. The MSC markers of CD73, CD90 and CD105, were also expressed. The MSC culture was also able to differentiate into adipocytes, chondrocytes, and osteocytes. Based on these results, white adipose tissue from Macaca fascicularis was found to have potential as a source of MSC.